Lactobacillus plantarum-derived cytoplasmic membrane vesicles as novel anti-inflammatory nanotherapeutics for psoriasis management - Xie, Yuedong; Lv, Guowen; Su, Dandan; Li, Manchun; Xu, Quanle; Chen, Hongbo; Cheng, Fang; Dai, Dongling (Frontiers in Immunology, 2025)
IntroductionCurrent research underscores the critical role of the gut-skin axis in inflammatory skin disorders such as psoriasis, with growing interest in the therapeutic application of probiotics. Despite this promise, the specific mechanisms and bioactive compounds through which probiotics exert their effects remain poorly characterized. In this study, we aimed to systematically evaluate the therapeutic potential of Lactobacillus plantarum (Lp)-derived bioactive fractions in psoriasis, with a particular focus on identifying key anti-inflammatory and immunomodulatory metabolites.MethodsThe microbiome characteristics of psoriasis were analyzed through open microflora data mining and bibliometrics, and the probiotics with potential therapeutic effects were identified. Four bioactive fractions from L. plantarum were extracted and characterized. CCK-8, qPCR, and flow cytometry were used to evaluate the effects of four bioactive components on oxidative stress in keratinocytes and inflammatory responses in macrophages. Metabolomics was used to analyze the metabolic profiles of bioactive components with anti-inflammatory and antioxidant properties, and to screen and identify the main metabolite that play a role. To evaluate the efficacy and safety of bioactive components in the treatment of IMQ-induced psoriasis in mice.ResultsA common feature of downregulation of Lactobacillus abundance was shown in patients with four inflammatory skin diseases including psoriasis. Four bioactive fractions, namely cytoplastic membrane vesicles (CMVs), bacterial lysate supernatant (BL-S), bacterial lysate precipitate (BL-P) and cell-free fermentation supernatant (CFS), were extracted from L. plantarum ATCC BAA-793, and CMVs were identified as having typical extracellular vesicles. In efficacy evaluation, CMVs and BL-S significantly reduced the mRNA levels of inflammatory factors in macrophages and the ROS levels of inflamed keratinocytes, among which CMVs had a more significant anti-inflammatory effect and had a unique inhibitory effect on M1 polarization of macrophages. Metabolomics revealed significant differences in metabolite profiles between CMVs and BL-S, and AEA enriched in both played anti-inflammatory, antioxidant and inhibitory roles in macrophage M1 polarization. In IMQ-induced psoriasis mouse models, CMVs demonstrated superior effects over BL-S in anti-hyperkeratosis, inhibiting inflammatory factor production, and down-regulating the proportion of M1 macrophages in skin and spleen. Both showed good biosafety in vivo.DiscussionThis study demonstrates that L. plantarum-derived CMVs, enriched with AEA, ameliorate psoriasis through multi-faceted mechanisms including anti-inflammation, antioxidative stress reduction, and reprogramming of macrophage polarization. These findings not only position bacterial nanovesicles as a novel cell-free therapeutic strategy for inflammatory skin diseases but also establish a functional screening platform for precision microbiome-based interventions.